BIBLIOMETRIC ANALYSIS OF THE APPLICATION OF ADMINISTRATIVE SANCTIONS FOR FOREIGNERS VIOLATING VISITATION VISAS IN INDONESIA (A STUDY OF LAW NUMBER 9 OF 1992 ON IMMIGRATION) - Mukmin Muhammad (Meraja journal, 2024)
[Full Paper] to pdf Copyright (c) 2024 Meraja journal